(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Companies must, in the present modern times of great changes and requirements, adapt continuously to consumer preferences, in order to remain competitive. Companies are striving to change consumer perception with brand positioning, they would like to draw their attention, ofer them everything they whish for and simply beacuse they are trying to become the best in their field. However, all of this is not possible without employees, their knowledge, skills and motivation to carry out their work which can be obtained in various ways. This paper introduces the results of research in which we analyse the effectiveness of positioning the brand in the eyes of consumers and managers in the studied company and the importance of knowledge management in this process. Our results confirm the good brand positioning, which the respondents confirmed, slightly lower estimate of the assigned point-brand was received from guests that came from abroad. For the company to effectively position their brand abroad, it is necessary to know the employees, which are a key factor in the situation of the company, its visibility and positioning. It is important that the employees use knowledge management system and than capture, discover, share and use received knowledge.